Natural History of Malignant Bone Disease in Renal Cancer: Final Results of an Italian Bone Metastasis Survey - Santini, Daniele (Public Library of Science, 2013)
BACKGROUND: Bone metastasis represents an increasing clinical problem in advanced renal cell carcinoma (RCC) as disease-related survival improves. There are few data on the natural history of bone disease in RCC. PATIENTS AND METHODS: Data on clinicopathology, survival, skeletal-related events (SREs), and bone-directed therapies for 398 deceased RCC patients (286 male, 112 female) with evidence of bone metastasis were statistically analyzed. RESULTS: Median time to bone metastasis was 25 months for patients without bone metastasis at diagnosis. Median time to diagnosis of bone metastasis by MSKCC risk was 24 months for good, 5 months for intermediate, and 0 months for poor risk. Median number of SREs/patient was one, and 71% of patients experienced at least one SRE. Median times to first, second, and third SRE were 2, 5, and 12 months, respectively. Median survival was 12 months after bone metastasis diagnosis and 10 months after first SRE. Among 181 patients who received zoledronic acid (ZOL), median time to first SRE was significantly prolonged versus control (n = 186) (3 months vs 1 month for control; P<0.05). CONCLUSIONS: RCC patients with bone metastasis are at continuous risk of SREs, and in this survey ZOL effectively reduced this risk.